2010
DOI: 10.1080/02724630903409204
|View full text |Cite
|
Sign up to set email alerts
|

A new small short-snouted dyrosaurid (Crocodylomorpha, Mesoeucrocodylia) from the Paleocene of northeastern Colombia

Abstract: Prior to this study, specimens from South America have been limited to a few fossils with only two taxa diagnosed. We describe a nearly complete skull and unassociated mandible of a new dyrosaurid, Cerrejonisuchus improcerus gen. et sp. nov., from the Paleocene Cerrejón Formation of northeastern Colombia. The skull of C. improcerus has relatively elongate supratemporal fenestrae and well-developed occipital tuberosities, both diagnostic characteristics of Dyrosauridae. The rostrum of adult C. improcerus compri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
106
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(110 citation statements)
references
References 31 publications
1
106
1
2
Order By: Relevance
“…The alveolar edges of d4 are higher than the edges of the other alveoli. The d7 alveoli are reduced and close to the eighth alveoli border as described for D. maghribensis (OCP DEK-GE 253) (Jouve et al, 2006) and C. improcerus (UF/IGM 29) (Hastings et al, 2010); this pattern was also found in an unidentified dyrosaurid, VPL/JU/IR/400, from Maastrichtian strata in India (Khosla et al, 2009). The tenth alveolus is not preserved on the right side of the dentary.…”
Section: Description and Comparisonmentioning
confidence: 76%
See 3 more Smart Citations
“…The alveolar edges of d4 are higher than the edges of the other alveoli. The d7 alveoli are reduced and close to the eighth alveoli border as described for D. maghribensis (OCP DEK-GE 253) (Jouve et al, 2006) and C. improcerus (UF/IGM 29) (Hastings et al, 2010); this pattern was also found in an unidentified dyrosaurid, VPL/JU/IR/400, from Maastrichtian strata in India (Khosla et al, 2009). The tenth alveolus is not preserved on the right side of the dentary.…”
Section: Description and Comparisonmentioning
confidence: 76%
“…The siphonial foramen is lacking in the medial view in this specimen, as in Guarinisuchus munizi. In contrast to this feature, Rhabdognathus aslerensis Jouve, 2008 (CNRST-SUNY-190) (Brochu et al, 2002) and Cerrejonisuchus improcerus (UF/IGM 29) (Hastings et al, 2010) share the condition of presence of the siphonial foramen in medial view. Mandible.…”
Section: Description and Comparisonmentioning
confidence: 78%
See 2 more Smart Citations
“…An additional approach was applied to this generic data set for further refinement of the diversity: phylogenetic correction, superimposed on the stratigraphy by filling ghost ranges of genera (Supplementary Data 1). Phylogenetic corrections follow the topology recovered for Thalattosuchia 31 and the topology recovered for Dyrosauridae 34 . Pholidosauridae (two marine genera) are, in comparison with Thalattosuchia and Dyrosauridae, a relatively small marine radiation with a larger ancestral freshwater stock.…”
Section: Methodsmentioning
confidence: 99%